Study of the Social and Development Characteristics of Irrigated Vegetable Farmers in As-Swaida Governorate. (Damascus University Journal of agriculture sciences, 2024)
The research aimed to study the social and developmental characteristics of irrigated vegetable farmers in Swaida; it was based on preliminary data through a questionnaire that targeting irrigated vegetable farmers during 2019- 2020 season, with a total sample size of 106 farmers. The results showed: that the enrolment rate in basic and secondary education for the 6-18 age group is very high at 91.76%, and therefore the dropout rate from schools is only 8.24%. and the agricultural exploitation rate of 61.89% in the study sample, shows that there is a surplus of space that can be managed and introduced into the productive process. The results showed seven factors of eleven independent variables, which had the greatest impact in distinguishing the groups of the proposed developmental scale (weak, acceptable, medium, good), which are: Age and experience of the farmer, number of family members, size of holding, number of machines, type of work, education level. Through the discriminatory function, it was found that the greatest influence in the proposed development scale is the size of the holding, followed by the level of education of the farmer, and then the age of the farmer, Also, the proposed discriminatory function corrected thereclassification with a rate of 98.1%. The study recommended supporting and adopting a policy of not agricultural land Fragmentation, as large investment projects are more profitable, and lead to improve the lives of farmers, in addition to managing surplus areas and incorporating them into the production process by integrating plant and animal projects with the vegetable projects.
Keywords: Irrigated Vegetables; Discriminatory Function; Development Indicators; Swaida